2011
DOI: 10.2135/cropsci2010.01.0036
|View full text |Cite
|
Sign up to set email alerts
|

North American Bristlegrass Seed Yield Response to Nitrogen Fertilizer and Environment

Abstract: Information on field management practices for seed production of newly domesticated grasses native to the southern Great Plains of North America has not been well documented. This study was conducted to document seed yield responses of one accession of plains bristlegrass [Setaria vulpiseta (Lam.) Roem. & Schult.] and three accessions of streambed bristlegrass [Setaria leucopila (Scribn. & Merr.) K. Schum.] to 0, 50, 75, 100, and 140 kg N ha−1 yr−1 under irrigation at Stephenville and Beeville, TX, during 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Singularly, there is evidence that heavier tillers and good N nutrition showed the greatest potential for flowering and seed production, in warm-season grasses (Canto et al, 2012). In a study with several newly native grasses, López-García et al (2011) found that inflorescence density was positively correlated to seed yield. Because of the high correlation of the PTN and greater ease of determination, this characteristic is the most appropriate indicator of ASY and PSY.…”
Section: Resultsmentioning
confidence: 99%
“…Singularly, there is evidence that heavier tillers and good N nutrition showed the greatest potential for flowering and seed production, in warm-season grasses (Canto et al, 2012). In a study with several newly native grasses, López-García et al (2011) found that inflorescence density was positively correlated to seed yield. Because of the high correlation of the PTN and greater ease of determination, this characteristic is the most appropriate indicator of ASY and PSY.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of N in the production of high yields of grass crops is well documented for various species (Fairey and Lefkovitch, 1998; Cookson et al, 2000; López‐García et al, 2011; Koeritz et al, 2013). In the present study, however, N application did not increase seed yield.…”
Section: Discussionmentioning
confidence: 99%